Inoculant and urea-molasses additives for forage sorghum silage - Hinds, M.; Brethour, J.; Bolsen, K. (Kansas State University. Agricultural Experiment Station, 2010)
Inoculant (1177 in one trial) and non-protein nitrogen (LSA-100 in two trials) silage additives were evaluated with whole-plant forage sorghum silage. Steers fed LSA-100 silage gained faster than steers fed control silage supplemented with soybean meal (4.8% in trial 1; 12% in trial 2). Feed conversion was improved 11% in trial 1 and was similar to the control silage in trial 2. Silage inoculated with 1177 supported rates and efficiencies of gain similar to the control silage. Of the nitrogen added from LSA-100, 90.9% in trial 1 and 86.2% in trial 2 was recovered from the concrete stave silos. Dry matter recoveries averaged 6.0 percentage units less for LSA-100 silages than controls, however 1177 increased recovery by 2.65 units. In general, silage from the bottom half of each silo was far more stable in air than that from the top half. The additives did not consistently affect aerobic stability.
Keywords: Beef; Inoculant; Urea-molasses; Sorghum silage